The importance of endoscopic spinchterotomy in biliary fistulas secondary to hydatid disease of liver - , M. Mahir Özmen, Adil TANIK, Arife POLAT, Uğur YILMAZ, Burhan ŞAHİN (Turkish Journal of Gastroenterology 1, 2019)
-